(untitled) (Research, Society and Development, 2021)
The effects of defoliation frequency (28, 35, 42 and 49 days) and defoliation intensity (30, 40 and 50 cm above the ground) on green dry matter (GDM) yield, and chemical composition of Panicum maximum cv. Mombaça were evaluated under natural field conditions at the Roraima´s savannas. Defoliation regimes affect productivity and chemical composition of grass forage. The decrease in the pasture defoliation frequency and intensity improved the accumulation of forage, however it reduces the tissue concentrations of N, P, Ca, Mg and K. Irrespective of defoliation frequencies, the highest levels of N (23.99 g kg-1), P (2.12 g kg-1), Ca (4.22 g kg-1), Mg (2.87 g kg-1) and K (21.45 g kg-1) were recorded for the defoliation intensity at 40 cm above the ground. The use of defoliation frequency around 42 days and defoliation intensity of 42,9 cm above the ground can be considered adequate for the management of pastures of P. maximum cv. Mombaça, in order to provides higher forage productivity and quality, regrowth vigor, larger efficiency of forage utilization, greater tissue renewal and canopy structure more favorable to grazing.